Correlation of MCT1 and ABCC2 gene polymorphisms with valproic acid resistance in patients with epilepsy on valproic acid monotherapy. Issue 3 (June 2019) - Chen, Juan; Su, Qibiao; Qin, Jiaming; Zhou, Yi; Ruan, Honglian; Chen, Ziyi; Chen, Zhuojia; Li, Hongliang; Zhou, Yafang; Zhou, Shan; Wang, Xueding; Zhou, Liemin; et al.
Abstract: Valproic acid (VPA) is used as one of the first-line antiepileptic drugs to control seizure in epilepsy patients. However, one third of patients do not respond to VPA. This study is to investigate the influence of single nucleotide polymorphisms (SNPs) in multidrug transporters on VPA responses in Han Chinese epilepsy patients on VPA monotherapy. Twelve SNPs involved in VPA transport pathways, including ABCC2, ABCC4, ABCG2, MCT1, MCT2 and OATP2B1 were genotyped in 153 Han Chinese epilepsy patients. We found that among all the patients, MCT1 rs60844753 CC carriers have higher incidence of VPA-resistance than CG carriers (P = 0.05), and in subgroup of generalized seizure, ABCC2 rs3740066 CC carriers had higher frequency of VPA resistance than TC + TT carriers (P = 0.03). Although other SNPs were not correlated with VPA resistance, significant ethnic difference was found in minor allele frequency of these SNPs, indicating that the influence of these SNPs on VPA efficacy should be broadly investigated in other ethnic populations. This study provides nominal evidence that SNPs of genes involved in the transport of VPA contribute to interpatient variation in VPA response. Although the associations were abolished after Bonferroni correction, the results provide an incentive for further research in sufficiently large samples. Graphical abstract: In all patients, MCT1 rs60844753 CC, and in patients with generalized seizure, ABCC2 rs3740066 CC was correlated with VPA resistance in patients with epilepsy on VPA monotherapy.